2015
DOI: 10.1002/acp.3178
|View full text |Cite
|
Sign up to set email alerts
|

Confidence and Eyewitness Identifications: The Cross‐Race Effect, Decision Time and Accuracy

Abstract: SummaryParticipants encountered same‐race and cross‐race faces at encoding, completed a series of line‐up identification tests and provided confidence ratings by using one of nine different confidence scales. Confidence was less well calibrated with identification accuracy when participants selected a cross‐race than a same‐race face because of overconfidence. By contrast, there was no cross‐race effect on confidence–accuracy calibration when participants responded ‘not present’. Whereas confidence was a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
79
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 48 publications
21
79
2
Order By: Relevance
“…In conclusion, replicating and expanding on previous findings (Dodson & Dobolyi, 2015a ; Tekin & Roediger, 2017 ), we demonstrated that the verbal scales with relatively few values used by police departments lead to CA relationships similar to those of more fine-grained scales. Providing numeric labels for verbal scales did not improve the CA relationship.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, replicating and expanding on previous findings (Dodson & Dobolyi, 2015a ; Tekin & Roediger, 2017 ), we demonstrated that the verbal scales with relatively few values used by police departments lead to CA relationships similar to those of more fine-grained scales. Providing numeric labels for verbal scales did not improve the CA relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Dodson and Dobolyi ( 2015a ) showed that providing verbal or numeric labels and varying the number of confidence points on a 100-point scale (6 points: 0, 20, 40, 60, 80, 100; or 11 points: 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100) did not change the CA relationship for eyewitness identification. Nonetheless, they employed a 100-point scale, which is unlikely to be used by police departments.…”
Section: Significancementioning
confidence: 99%
“…The sample of nonchoosers and the rejection data referred to were described in Sauerland et al [ 33 ]. Following other researchers [ 17 , 20 , 45 ], we report results for the thief and victim showup combined. This is in accordance with the idea of stimulus sampling [ 17 , 46 ] and ensures a more stable representation of the associations displayed.…”
Section: Resultsmentioning
confidence: 99%
“…A consistent finding is that estimator variable manipulations largely do not negatively impact the overall CA relationship. Indeed, manipulations of weapon presence (Carlson, Dias, Weatherford, & Carlson, 2017), exposure time (Carlson et al, 2016; Palmer, Brewer, Weber, & Nagesh, 2013), retention interval (Sauer, Brewer, Zweck, & Weber, 2010), and race (Dodson & Dobolyi, 2016) have all shown that regardless of condition, accuracy increases with confidence, and highly confident eyewitnesses tend to be highly accurate.…”
Section: The Confidence–accuracy Relationshipmentioning
confidence: 99%